THE TEXT OF PURANA PURA HULUNDANU BATUR KINTAMANI PRADESA SONGAN KINTAMANI BANGLI STRUCTURE ANALYSIS, FUNCTION AND MEANING - Fajar Pramesta, Agus (Humanis; Volume 12. No.1. Juli 2015, 2015)
This research analyzed about Text of Purana Pura Hulundanu Batur, Kintamani with the analysis of the structure, functions, and the meaning. This analysis aimed to uncover the intrinsic structure which contain into Purana Pura Hulundanu Batur, Kintamani. In other ways, the writer wants to uncover the functions and also the meaning which shared by the writer through Purana Pura Hulundanu Batur Kintamani. This analysis used structural theory. Structural theory applied some combination and proposed by the author of literature expert. Such as: Ratna, Endraswara, Teeuw and Luxemburg. The method and technique used in this analysis categorized into three steps: 1) preparation of the data which used identity method and based on library studies. 2) the preparation of the data applied qualitative method and also applied descriptive technique. 3) the step of presenting the result analysis which applied formal and nonformal method. The finding on this research is an explanation of the meaning and purana that is one part of oldish literature as like as a legend, and then it is known a narrative structure which consist of the legalization theme and possessing theme, and also there is an incidence that make the story in these Purana. In this incident figured by some characters of gods and the ascetics. Where located at Songan village, Kintamani. The incident happened by all characters which shared on the text Purana Hulundanu Batur. In this analysis found that Purana Pura Hulundanu Batur, Kintamani is about social and religiousness. in other way, in analysing the meaning of this Purana known the meaning in doing the ritual and the understanding because of god favor.
Keywords: Purana, Structure, Functions and Meaning